An Infeasible Interior-Point Algorithm for Stochastic Second-Order Cone Optimization - Alzalg, Baha; Badarneh, Khaled; Ababneh, Ayat (Journal of optimization theory and applications, 2019)
Alzalg (J Optim Theory Appl 163(1):148–164, 2014 ) derived a homogeneous self-dual algorithm for stochastic second-order cone programs with finite event space. In this paper, we derive an infeasible interior-point algorithm for the same stochastic optimization problem by utilizing the work of Rangarajan (SIAM J Optim 16(4), 1211–1229, 2006 ) for deterministic symmetric cone programs. We show that the infeasible interior-point algorithm developed in this paper has complexity less than that of the homogeneous self-dual algorithm mentioned above. We implement the proposed algorithm to show that they are efficient.